2011
DOI: 10.3109/10398562.2011.583077
|View full text |Cite
|
Sign up to set email alerts
|

Reaching the Hard-To-Reach: How Information Communication Technologies Can Reach Young People at Greater Risk of Mental Health Difficulties

Abstract: ICT offers relevant and innovative strategies for young people at increased risk of developing mental health difficulties. Whilst many young people experience social isolation and stigma, the manifestation of these issues and the strategies required to address them vary. ICT-based programs will benefit from identifying which protective factors can be most positively influenced through the unique properties of ICT, amongst whom and how. Challenges to ICT-based health services include inadequate access and train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 8 publications
1
20
0
1
Order By: Relevance
“…Individuals with mental health conditions are increasingly turning to the Internet for information, advice, support, and to share their experiences [12]. They are increasingly expect eMental Health options as part of their care [13, 14] and report high levels of technology device use [15] in their everyday lives.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with mental health conditions are increasingly turning to the Internet for information, advice, support, and to share their experiences [12]. They are increasingly expect eMental Health options as part of their care [13, 14] and report high levels of technology device use [15] in their everyday lives.…”
Section: Introductionmentioning
confidence: 99%
“…Wilson and colleagues [21] identified that young people have a strong desire for autonomy, believing they should solve problems for themselves. In terms of these barriers, Internet services have several advantages: no geographical boundaries, services are generally free to the user, and the Internet is largely anonymous and private, which is likely to reduce the stigma and embarrassment associated with seeking help [22]. The interactive nature of the Internet allows for the provision of online therapies in various forms such as games or eLearning websites [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…It was established that social network is important to express identity, which varies from male to female. Social network is essentially flexible to promote individual ethic and customs [6,7,19,32,35]. Furthermore, individuals can express their views and opinions with their friends or other supports in critical peer based sociality [37] .…”
Section: Literature Reviewmentioning
confidence: 99%